Development of Taman Ghanjaran Tourist Village from the Perspective of Dynamic Governance in Ketapanrame Village, Trawas District, Mojokerto Regency - Sri Roekminiati; Sapto Pramono; Ika Devi Pramudiana; Rayhan Al Ghavara Heda; Firdiansyah Arief Arianto (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to describe and analyze the development of the Taman Ghanjaran tourist village in Ketapanrame, managed by BUMDesa